The "forgotten" middle class: An analysis of the effects of globalisation - Regina Pleninger; Jakob de Haan; Jan-Egbert Sturm (ETH Zurich, KOF Swiss Economic Institute, 2019)
This paper studies the effects of globalisation on the income share of the middle class. Our findings suggest that globalisation, proxied by the KOF Economic Globalisation Index, reduces the income share of the middle class. The income share of the poorest 20% also drops due to globalisation, while that of the richest 20% increases. When we distinguish between de facto and de jure globalisation, we find that only de facto measures have statistically significant effects on income shares and inequality measures. Our results are robust for alternative definitions of the middle-class income share and hold for trade and financial globalisation.
hdl:20.500.11850/383388
Keywords: D31; F62; I24; O15; 330; middle class; income inequality; globalisation; income shares